Verbal incontinence and the failure of the Second Spanish Republic. Irresponsible political discourse and its contribution to the outbreak of the Civil War in Spain - Chalupa, Jiří (Romanica Olomucensia, 2016)
The intention of this paper is to show how much the tragic failure of the Second Spanish Republic was the result not only of the economic, social, and international situation, but also the totally irresponsible behaviour of many of the main political actors in the 'thirties. Some speeches of Manuel Azaña, Francisco Largo Caballero, José María Gil Robles, and José Antonio Primo de Rivera will be analysed in order to show how much those iconic characters let themselves be seduced by their own words, speaking in a very reckless manner without thinking of the possible consequences of such diatribes. Some of those personalities were being changed into fictional characters to a certain point, perhaps even parodic - products of their own verbiage: Largo Caballero into a "Madrid Lenin", Gil Robles into a "Spanish Mussolini", José Antonio into an "out-and-out fascist". The power of the propaganda word, which is often underestimated and which can cause real disasters simply because the speakers, powered by the energy of an excited crowd, do not know when to stop, will be highlighted. How some terms, for example "anti-Spain", can carry so much explosive and destructive cargo that their widespread use can lead almost inevitably to a conflict of unexpected dimensions, in our case the Spanish Civil War, will be shown.
Keywords: Spanish History; Second Spanish Republic; Spanish Civil War.